Side Scan Versus Multibeam Echosounder Object Detection: A Comparative Analysis - Brissette, Mike B.; Clarke, John E. (The International Hydrographic Review, 2015)
The undisputed remote sensing tool for detailed sea floor object detection is the side scan sonar. From pipelines, to downed aircraft, to mines, a side scan sonar’s unique characteristics effectively ensonify and subsequently display these objects. For bathymetry, the Multibeam Echosounder (MBES) has quickly proven its superior capabilities. An MBES’s unique characteristics allow it to provide 100 per cent ensonification of the sea floor while meeting or even exceeding IHO specifications. During the 1997 Coastal Multibeam Sonar Training Course in Victoria, BC, inert mines were laid at different depths and then ensonified by a side scan sonar and an MBES. The aim of this exercise was to compare the detection characteristics of the two sonars using one of the inert mines. This paper is a discussion of that comparison and the lessons learned. Comparative imagery is used to illustrate the success of each sonar in illuminating the mines to the operator. Unaided visual detection is not always the most efficient method for finding objects in large quantities of MBES data; therefore, subtractive temporal analysis was implemented in order to enhance the MBES object detection process. As well, a simple automated detection algorithm was used successfully on the temporally differenced images. The background, implementation and results of the MBES subtractive analysis performed in the area of the inert mine will be compared to the detection achieved using the side scan sonar. Finally, conclusions will be drawn as to the efficacy of the MBES as an object detection sonar.